In the End… (Symphony in the Flint Hills, 2013)
A quote by poet/conservationist Baba Dioum of Senegal, pages for notes, and a plat of the military Reserve at Fort Riley from 1855, surveyed and drawn by Francis T. Bryan, Lt. Top. Engrs.
Keywords: Baba Dioum; Fort Riley; Kansas; plat